2020
DOI: 10.1039/d0cp03276j
|View full text |Cite
|
Sign up to set email alerts
|

Shining light on the electronic structure and relaxation dynamics of the isolated oxyluciferin anion

Abstract: Firefly bioluminescence is exploited widely in imaging in the biochemical and biomedical sciences; however, our fundamental understanding of the electronic structure and relaxation processes of the oxyluciferin that emits the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…13 Our observation of positive β 2 values at eKEs ≤ 0. the photoelectron spectra of DF-HBDI − supports this suggestion; however, we cannot completely rule out that the feature at 0.4 eV corresponds to autodetachment from the nearby 1nπ * state. A recent study has suggested that dipole bound states may be populated by IC from higher lying electronic excited states 68 and previous slow electron velocity map imaging (SEVI) studies of phenoxide and uracil deprotonated anions have demonstrated that vibrational autodetachment signal from dipole bound states can influence the photoelectron angular distributions; 77,78 therefore we cannot rule out a contribution from a dipole bound state of DF-HBDI − . However, the vibrational autodetachment process from the dipole bound states observed in the SEVI spectra of phenoxide and uracil gave rise to isotropic photoelectron distributions, which obscured anisotropic PADs from non-resonant detachment, 77,78 which contrasts with the highly anisotropic distribution we observe in our photoelectron spectra of DF-HBDI − at low eKEs.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…13 Our observation of positive β 2 values at eKEs ≤ 0. the photoelectron spectra of DF-HBDI − supports this suggestion; however, we cannot completely rule out that the feature at 0.4 eV corresponds to autodetachment from the nearby 1nπ * state. A recent study has suggested that dipole bound states may be populated by IC from higher lying electronic excited states 68 and previous slow electron velocity map imaging (SEVI) studies of phenoxide and uracil deprotonated anions have demonstrated that vibrational autodetachment signal from dipole bound states can influence the photoelectron angular distributions; 77,78 therefore we cannot rule out a contribution from a dipole bound state of DF-HBDI − . However, the vibrational autodetachment process from the dipole bound states observed in the SEVI spectra of phenoxide and uracil gave rise to isotropic photoelectron distributions, which obscured anisotropic PADs from non-resonant detachment, 77,78 which contrasts with the highly anisotropic distribution we observe in our photoelectron spectra of DF-HBDI − at low eKEs.…”
Section: Discussionmentioning
confidence: 81%
“…11,13 Electrons resulting from autodetachment processes from electronic excited states above the detachment threshold commonly give rise to features with constant eKE as a function of wavelength in the photoelectron spectra of anions, and results from the propensity for vibrational energy to be retained on autodetachment. 5,7,11,[13][14][15]18,57,[60][61][62][63][64][65][66][67][68] To identify the presence of weaker features in the spectra, we subtracted the 364 nm spectrum (which contains predominantly direct detachment signal) from the spectra at all other wavelengths, to produce difference spectra which reveal all features resulting from indirect detachment processes; these are presented in Fig. S1 in the ESI † .…”
Section: Photoelectron Spectramentioning
confidence: 99%
“…This suggested the presence of anion excited states above the detachment threshold that were resonantly excited by the photodetachment laser. Such anion excited states, which are related to the transient resonances observed in electron loss spectroscopy, have also been observed in the related anthracenyl anion and other similar PAHs. …”
Section: Introductionmentioning
confidence: 73%
“…Again, this was observed for rhodamines, oxazines, and smaller ionic dyes with the xanthene core structure. 25,27 It should be mentioned that the photon energies are all well below the vertical detachment energy (3.26 eV), 23 and electron photodetachment is not an open channel.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the ketone absorbs maximally at ≈540 nm and the enol at ≈475 nm, but that the spectra in both cases are broad and somewhat overlap. Fielding and co-workers 23 did photoelectron spectroscopy and reported electron binding energies of the different isomeric forms of the monoanions. As in the earlier work, we have here included dimethylated oxyluciferin ( dm-OL − , Fig.…”
Section: Introductionmentioning
confidence: 99%